Effectiveness of adding a peak flow meter for the identification of patients with chronic obstructive pulmonary disease in real-world clinical practice - Hideki Ikeda (BMC Pulmonary Medicine)
Abstract Peak expiratory flow (PEF) measurement is useful for detecting moderate and severe chronic obstructive pulmonary disease (COPD). We aimed to validate its combined effectiveness with a questionnaire and to determine appropriate cutoff values in Japan. Outpatients aged ≥ 60 years with a smoking index ≥ 400 cigarette-years receiving non-respiratory treatment and patients with COPD receiving regular treatment underwent PEF measurements and pulmonary function tests. Receiver operating characteristic (ROC) curves were created to differentiate between the percentage forced expiratory volume in 1 s (%FEV1) values above or below 80%, based on PEF values normalized by height (method A) and height squared (method B). Of 98 patients, COPD was confirmed in 15 (15.3%). The reference values used to estimate %FEV1 < 80% derived from the ROC curve were 2.40 and 1.37 for methods A and B, respectively. Both methods had a high area under the ROC curve (0.92) (p < 0.001). The number of suspected COPD (sCOPD) cases was narrowed down from 98 to 33 and 27 using methods A and B, respectively. The combination of the COPD questionnaire and peak flow meter can effectively differentiate severe from the more severe half of moderate COPD from sCOPD cases and improve diagnosis of asymptomatic COPD cases that may require medication prescription by general practitioners.